2020
DOI: 10.1002/aic.16253
|View full text |Cite
|
Sign up to set email alerts
|

Protic ionic liquid‐based deep eutectic solvents with multiple hydrogen bonding sites for efficient absorption of NH3

Abstract: The emerging of ionic liquids (ILs) provides an efficient and sustainable way to separate and recover NH 3 due to their unique properties. However, the solid or highly viscous ILs are not suitable for traditional scrubbing. Therefore, an effective strategy was proposed by combining the protic ILs (PILs) with acidic H and low viscous ethylene glycol (EG) to form IL-based deep eutectic solvents (DESs) for NH 3 absorption. The results indicated that these PIL-based DESs not only have fast absorption rate, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Therefore, the effect of water on NH 3 solubilities in metal‐based DESs prepared in this work is very minor. Table 2 presents the comparison of NH 3 solubilities in different DESs and ILs 25,36–50,65–76 . It is found that the solubilities of NH 3 in metal‐based DESs prepared in this work are remarkably high, especially at low pressures.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, the effect of water on NH 3 solubilities in metal‐based DESs prepared in this work is very minor. Table 2 presents the comparison of NH 3 solubilities in different DESs and ILs 25,36–50,65–76 . It is found that the solubilities of NH 3 in metal‐based DESs prepared in this work are remarkably high, especially at low pressures.…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, DESs have the potential to replace ILs for highly efficient and reversible gas absorption. [31][32][33][34][35] As for the application of DESs in reversible NH 3 absorption, there have been some impressive examples such as ChCl + PhOH + EG DESs, 36 NH 4 SCN + Gly DESs, 37 EaCl + Gly DESs, 38 ChCl + TetrZ + EG DESs, 39 MAA + TetrZ DESs, 40 [Im][NO 3 ] + EG DESs, 41 [emim]Cl + BenTriz DESs, 42 [ImH] Cl + Gly DESs, 43 LiCl/EG DESs, 44 and [MeC OH 3 N]Cl/U. 45 After careful examination on these DESs, it can be found that they are typically constituted by one weak acidic compound (e.g., PhOH, NH 4 46 EaCl + Res DESs, 47 and [TMPDA]Cl 2 + PhOH DESs 48 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction efficiency of sulfur compounds depends on the alkyl-chain length of the HBA; for example, the DES with longer alkyl chain length on the HBA had a higher thiophene distribution capacity. Warrag et al [ 128 ] found very high selectivity (higher than that of ILs and DESs) for thiophene using TEAC/gly (1:2) DES but the distribution capacity was lower using the same glycerol but DESs. When glycerol was replaced with EG in the DES, higher distribution coefficient was achieved compared to glycerol-based DES owing to the higher thiophene solubility in the EG-based DES.…”
Section: Desulfurization and Denitrification Of Fuelsmentioning
confidence: 99%
“…Compared with the traditional solvent ILs, most of DESs exhibit a lot of remarkable advantages such as desirable biodegradability, environmental friendliness, ease of preparation for large‐scale applications, and show great interests in many fields 17,19 . DESs have been widely used in the extraction separations, 19 natural products extraction, 20 gaseous mixture separations, 21,22 catalysis, 23,24 dissolution and modification processes, 25 electrochemistry, 26 and material chemistry 27 . Jiang et al 28,29 have achieved a favorable separation performance in ethylene/ethane by a novel supported liquid membrane with DESs as the carrier.…”
Section: Introductionmentioning
confidence: 99%